2014
DOI: 10.1037/a0034456
|View full text |Cite
|
Sign up to set email alerts
|

Looming motion primes the visuomotor system.

Abstract: A wealth of evidence now shows that human and animal observers display greater sensitivity to objects that move toward them than to objects that remain static or move away. Increased sensitivity in humans is often evidenced by reaction times that increase in rank order from looming, to receding, to static targets. However, it is not clear whether the processing advantage enjoyed by looming motion is mediated by the attention system or the motor system. The present study investigated this by first examining whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 98 publications
2
26
0
1
Order By: Relevance
“…The use of accuracy as a potentially more sensitive measurement than RT has previously been noted by many authors. For instance, Santee and Egeth (1982) suggested that under the Bdata-limited^conditions (Norman & Bobrow, 1975) of briefly presented displays, accuracy measures are more sensitive to perceptual processes (see also Gellatly, Cole, Fox, & Johnson, 2003;Milliken & Tipper 1998;Rafal, Smith, Krantz, Cohen, & Brennan, 1990;Skarratt, Gellatly, Cole, Pilling, & Hulleman, 2014). Empirical support for this has come from Cole, Kuhn, Heywood, and Kentridge (2009), who showed that although color Bsingletons^do not automatically attract attention when RT is used to index capture, they do so when a Bone-shotĉ hange detection method is used.…”
Section: Methodsmentioning
confidence: 90%
“…The use of accuracy as a potentially more sensitive measurement than RT has previously been noted by many authors. For instance, Santee and Egeth (1982) suggested that under the Bdata-limited^conditions (Norman & Bobrow, 1975) of briefly presented displays, accuracy measures are more sensitive to perceptual processes (see also Gellatly, Cole, Fox, & Johnson, 2003;Milliken & Tipper 1998;Rafal, Smith, Krantz, Cohen, & Brennan, 1990;Skarratt, Gellatly, Cole, Pilling, & Hulleman, 2014). Empirical support for this has come from Cole, Kuhn, Heywood, and Kentridge (2009), who showed that although color Bsingletons^do not automatically attract attention when RT is used to index capture, they do so when a Bone-shotĉ hange detection method is used.…”
Section: Methodsmentioning
confidence: 90%
“…Many studies have suggested that motion direction does not attract attention, but motion onset does . Studies have also suggested that certain motion features such as looming are able to attract attention (Franconeri & Simons, 2003;von Grünau, Matthews, & Cavallet, 2010;von Mühlenen & Lleras, 2007;Wang et al, 2012), with special emphasis on looming motion as a relevant behavioral alert (e.g., sign of danger) or associated with a postattentional motor priming process (Skarratt et al, 2009(Skarratt et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, looming motion improves response preparation outside the attentive stage. In a subsequent study, Skarratt, Gellatly, Cole, Pilling, and Hulleman (2014) examined the visuomotor priming to looming motion across five experiments and provided strong evidence that looming and receding motion equivalently attracts attention, but the looming motion advantage is motoric rather than perceptual.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that because looming and receding motion grasp attention in a similar way, the looming bias is dependent on enhanced processing rather than on paying more attention. They suggested that this enhanced processing takes place in the motor system (Skarratt et al, 2014). Our results suggest that this enhanced processing is probably not based on conscious, complex, cognitive processes that are dependent on mental resources, but rather on a more automatic process, as the looming bias took place even when cognitive resources were reduced.…”
Section: Discussionmentioning
confidence: 67%
“…Skarratt, Gellatly, Cole, Pilling, and Hulleman (2014) have provided evidence that looming and receding motion attract attention equally. They concluded that because looming and receding motion grasp attention in a similar way, the looming bias is dependent on enhanced processing rather than on paying more attention.…”
Section: Discussionmentioning
confidence: 99%